Analysis of Problems in Learning Mathematics Based on Difficulties, Errors, and Misconceptions in the Material of Equations and Inequality Absolute Values of One Variable: Systematic Literature Review - Panjaitan, M. Azhari; Juandi, Dadang (KnE Social Sciences, 2024)
Problems in learning mathematics, there will be difficulties, errors, and student misconceptions during learning. This study aims to analyze problems in learning mathematics based on difficulties, errors, and misconceptions about the material of linear equations and inequalities of one variable. The method used in this research is a Systematic Literature Review (SLR). The population of this research is all Of the 30 journal articles obtained, then adjusted to the inclusion criteria and the sample consists of 15 relevant research results on problems in learning mathematics based on difficulties, errors, and misconceptions on the material of linear equations and inequalities of one variable. Samples were taken from indexed journals published in the period 2011-2021. The research question is how to describe problems in learning mathematics based on difficulties, errors, and misconceptions on the material of linear equations and inequalities of one variable based on the year of school, level of study, research location, and sample size. The SLR method can find mathematics learning problems with ten years of study. The results showed that students’ errors and misconceptions dominated learning outcomes in the problem of learning equations and inequalities absolute value of one of the variables. Most of the research was conducted at the junior high school level outside Java with a sample size of 30 people or more. Based on the results of the review, the conclusion of the study proves that students often experience errors when studying equations and inequalities of the absolute value of one variable. Keywords: learning mathematics based on difficulties, errors, and misconceptions, systematic literature review, the material of equations and inequality absolute values of one variable